Chemical bath deposition route for the synthesis of ultra-thin CuIn(S,Se)2 based solar cells. - Lugo Loredo, Shadai; Sánchez González, Yudania; Neuschitzer, Markus; Xie, Hai Bing; Insignares Cuello, Cristina; Izquierdo Roca, Victor; Peña Méndez, Yolanda; Saucedo, Edgardo (Elsevier, 2015)
CuIn(S,Se)2 (CISSe) photovoltaic grade thin films are usually grown by expensive vacuum based methods or chemical routes that require highly toxic precursors. In this work, we present the synthesis of CISSe absorbers by a simple chemical bath deposition (CBD) route. In the first step, In2S3/Cu2 − xS stack was deposited as a precursor by CBD on Mo-coated soda lime glass substrates, using respectively thioacetamide and N,N′ dimethylthiourea as S source. Then the CISSe thin films were synthesized by the precursor's selenization at 450 °C. The obtained films were characterized by X-ray diffraction (XRD), Raman spectroscopy and scanning electron microscopy (SEM). The tetragonal chalcopyrite structure of CISSe was identified by XRD and Raman, confirming that the major part of S was replaced by Se. SEM images show a compact and homogeneous film and by cross-section the thickness was estimated to be around 700 nm. Solar cells prepared with these absorbers exhibit an open circuit voltage of 369 mV, a short circuit current density of 13.7 mA/cm2 , a fill factor of 45% and an efficiency of 2.3%.